THE EFFECT OF LEVERAGE, PROFITABILITY AND SALES GROWTH ON TAX AVOIDANCE IN FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR 2020 – 2024 PERIOD - Retno Ginanjar; Iin Indarti Iin Indarti; Wenny Ana Adnanti; Tjandra Tirtono Tjandra Tirtono4 (Jurnal Akuntansi dan Bisnis, 2025)
This study aims to determine the effect of leverage, profitability, sales growth on tax avoidance of Food and Beverage companies listed on the IDX in 2017-2021. The type of research used in this research is comparative causal research. The calculated F value is 4.963 and a significant probability value of 0.003 is less than 5%, so it can be concluded that leverage, profitability, and sales growth simultaneously affect tax avoidance in Food and Beverage companies listed on the IDX in 2019- 2023. The results of the study show that partially leverage and profitability have a significant positive effect on tax evasion in food and beverage companies listed on the IDX in 2019 - 2023, while sales growth has no effect on tax evasion in food and beverage companies listed on the IDX in 2017 – 2021.